Menstrual Cycle Phase Modulates Auditory-Motor Integration for Vocal Pitch Regulation - Zhu, Xiaoxia; Niu, Yang; Li, Weifeng; Zhang, Zhou; Liu, Peng; Chen, Xi; Liu, Hanjun (Frontiers in Neuroscience, 2016)
In adult females, previous work has demonstrated that changes in auditory function and vocal motor behaviours may accompany changes in gonadal steroids. Less is known, however, about the influence of gonadal steroids on auditory-motor integration for voice control in humans. The present event-related potential (ERP) study sought to examine the interaction between gonadal steroids and auditory feedback-based vocal pitch regulation across the menstrual cycle. Participants produced sustained vowels while hearing their voice unexpectedly pitch-shifted during the menstrual, follicular, and luteal phases of the menstrual cycle. Measurement of vocal and cortical responses to pitch feedback perturbations and assessment of estradiol and progesterone levels were performed in all three phases. The behavioural results showed that the menstrual phase (when estradiol levels are low) as associated with larger magnitudes of vocal responses than the follicular and luteal phases (when estradiol levels are high). Furthermore, there was a significant negative correlation between the magnitudes of vocal responses and estradiol levels. At the cortical level, ERP P2 responses were smaller during the luteal phase (when progesterone levels were high) than the menstrual and follicular phases (when progesterone levels were low). These findings show neurobehavioural evidence for the modulation of auditory-motor integration for vocal pitch regulation across the menstrual cycle, and provide important insights into the neural mechanisms and functional outcomes of gonadal steroids’ influence on speech motor control in adult women.